Management of the Airway for Transoral Robotic Supraglottic Partial Laryngectomy - Stubbs, Vanessa C.; Rajasekaran, Karthik; Gigliotti, Adam R.; Mahmoud, Ahmad F.; Brody, Robert M.; Newman, Jason G.; Rassekh, Christopher H.; Weinstein, Gregory S. (Frontiers in Oncology, 2018)
Introduction: Over the last several decades, transoral resection techniques for treatment of supraglottic lesions have become increasingly favored to reduce the need for either open transcervical resection or primary chemoradiation. Transoral robotic surgery (TORS) offers advantages in visualization, dissection control, and access to remove bulky tumors en bloc. However, the management of the airway for these cases tends to vary, without clear guidelines as to when a tracheostomy is necessary. Materials and Methods: A retrospective review of all patients who underwent transoral robotic supraglottic partial laryngectomy at a large academic center from May 2005 through December 2016 was performed. Airway management was examined, specifically as it pertains to whether a tracheostomy was performed at the time of surgery or otherwise. Demographic and tumor characteristics were also evaluated. Results: Sixty-three patients were included. Forty (63%) were male, the average age at surgery was 63.6, and the majority (90.5%) underwent resection for squamous cell carcinoma of the supraglottis. Thirty-nine patients (62%) underwent the procedure with standard endotracheal intubation using a wire-reinforced tube. Of these, 4 patients required subsequent tracheostomy- 2 for laryngeal edema postoperatively, one for airway management during a postoperative bleeding event, and one for laryngeal edema following initiation of adjuvant chemoradiation. Twenty patients (32%) underwent tracheostomy at the time of transoral resection for airway management, 17 of whom were decannulated an average of 12.2 weeks following surgery. Those who underwent tracheostomy at the time of surgery had a higher percentage of tumors involving multiple supraglottic subsites (p = 0.031), 85% versus 54% in the group who did not undergo tracheostomy. No difference in age, BMI, clinical T-stage, or clinical N stage was found between the two groups. Conclusion: Performing a tracheostomy at the time of surgery should be considered for those patients with more extensive malignant disease (T2 tumors). While avoiding tracheostomy is often preferred by the patient, the maintenance of the patent airway peri-operatively should be first priority when considering airway management. Furthermore, as the majority of those patients receiving tracheostomy are decannulated within 4 months of surgery, the tracheostomy could be considered a short-term adjunct to the procedure.